Yang-Mills instantons on the taub-NUT space and supersymmetric N=2 gauge theories with impurities - O'Hara, Clare (Trinity College (Dublin, Ireland). School of Mathematics, 2010)
We write a formula for arbitrary charge calorons, instantons on R3 x S1, in terms of the Green's function of the Laplacian defined for the Nahm Transform, thus generalising the formula for the charge one caloron derived by Kraan and van Baal in [1]. The Laplacian is constructed from Nahm data. The usual approach to the Nahm Transform involves an integration over the interval on which the Nahm data are defined. By using Green's functions we avoid this integration and our formula is straightforward to use.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin.